Detrital zircon age signatures of the basal Cambrian sandstone unit in North China: implications for drainage divides during global Sauk transgression and separation from Gondwanaland. Issue 9 (15th May 2023) - Wei, Rong-Hao; Duan, Liang; Zhang, Xingliang; Meng, Qing-Ren; Zhan, Rong-Ruo; Ma, Chu-Xuan; Xu, Jing; Shi, Yi; Zhang, Xiao-Yin
ABSTRACT: The basal Cambrian sandstone unit in the North China craton (NCC) is an example of globally widespread siliciclastic succession that resides on the Great Unconformity and deposited on a hypothesized low-lying peneplain during the Cambrian global eustatic sea-level rise. Detrital zircon age signatures from this distinct sequence enable recognition of the ancient drainage system of the NCC in deep time and track its potential linkage with the Gondwana landmass. LA-ICP-MS U–Pb dating of the fossil-calibrated basal Cambrian (Series 2) detrital zircon samples from seven measured sections reveal marked spatial changes in their age signatures that can be divided into three distinct types. The first is generally characterized by the bimodal age populations with broad peaks at ~1.85 Ga and ~2.5 Ga that correlate with the Archean to Paleoproterozoic basement inboard of the NCC. The second is featured by multimodal distribution with diagnostic Neoproterozoic peaks that correspond to subregional magmatic record. The third also shows multiple-zircon age populations, but yields significant crystallization ages close to the early Cambrian age. Comparing our new data with existing age spectra for the Cambrian strata across the NCC and the northern Gondwana demonstrates that separate drainage systems did exist in the peneplained basement during global Cambrian transgression and the basal Cambrian unit in the NCC was not a part of the far-travelled sand sheet across the northern margin of Gondwana. The most suitable source for Cambrian-aged grains constrained by paleogeographic restoration is the arc terrane developed along the northern margin of the NCC as a result of subduction of the Paleo-Asian oceanic plate. Our new continental-scale detrital zircon provenance signatures in the basal Cambrian unit suggest that the NCC should be considered a discrete continental block separated by the Proto-Tethys Ocean in the Cambrian, rather than an integral part of the northern Gondwana. Graphical abstract: uf0001